PILIHAN ETIKAL DALAM MEMERANGI KEJAHATAN DI INDONESIA - Balthasar Watunglawar (LPPM Politeknik Saint Paul Sorong, 2021)
This study aims to find and explain efforts to embattle crime. The research was conducted with qualitative methods. Data obtained through interview and documentation techniques were collected for further condensation and conclusion. The results of the study inform that efforts to embattle crime are carried out in two ways, namely the way of evil and the way of goodness. The way of evil is the punishment that equals or burdens the perpetrators of crimes so that they are not sufficient in moral value, such as the death penalty for narcotics crimes, murder, and corruption. The second is the path of goodness. Evil must always be rewarded with good, as the moral imperative of Thomas Aquinas,